Analisis Karakteristik Marshall pada Beton Aspal Lapis Pengikat (Asphalt Concrete-Binder Course) menggunakan Aspal Modifikasi Serbuk Serat Pelepah Batang Pisang - Desi Widianty; Ratna Yuniarti; Akmaluddin Akmaluddin; Agung Prabowo; Shofia Rawiana (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2020)
Asphalt modification by adding fiber powder of banana stem can be implemented to improve the performance of pure asphalt. Asphalt concrete binder course AC-BC is a flexible pavement layer that functions to distribute the load towards the foundation layer. So it really needs strength, durability and stability of the materials. For that, it is necessary to use asphalt modification with fiber powder of banana stem which is used as a binding material in AC-BC asphalt concrete mixture. The proper percentage of modified asphalt level will determine the optimum quality of an asphalt mixture. Asphalt concrete specimens were made in 3 (three) samples for each variation of asphalt level by 5%; 5.5%; 6%; 6.5%; and 7%. The asphalt optimum level in the mixture is carried out through volumetric investigation in the form of VMA, VIM, and VFB values and mechanical assessment in the form of stability, flow and Marshall Quetient. The results of data analysis found that the value of VIM, stability and MQ tend to decrease with increasing levels of modified asphalt. On the other hand the value of VMA, VFB and flow tend to rise with increasing levels of modified asphalt. However, from the five variations of asphalt levels obtained asphalt levels of 5% and 5.5% which meet all the specifications of AC-BC asphalt concrete specification. To determine the asphalt optimum level, the average of qualified asphalt level is taken. So that the asphalt concrete AC-BC will produce a better structural performance at 5.25% asphalt level with banana stem fiber powder on asphalt by 0.1%.